Penerapan Model Pembelajaran Problem Based Learning (PBL) untuk Meningkatkan dan Hasil Belajar Siswa pada Materi Sistem Pencernaan Manusia di Kelas VI SDN 027 Danau Lancang - Pohan, Mantahari (Tematik: Jurnal Penelitian Pendidikan Dasar, 2023)
This study aims to determine the application of the problem-based learning model to improve student learning outcomes on human digestive system material in class VI of State Elementary School 027 Danau Lancang. The method used in this research is Classroom Action Research (PTK). This PTK uses the demonstration learning method. PTK consists of 5 stages, namely: planning, action, observation, reflection. The results showed: (1) By using the problem-based learning model, student learning outcomes in each cycle have increased significantly. Student learning outcomes in cycle I amounted to 80 with 95% completeness, cycle II amounted to 86 with 100% completeness. (2) Classical learning in cycle I was 78.61% increasing to 91.39% in cycle II and group learning from cycle I was 81.25% increasing significantly in cycle II to 100%.